Incidence of CNS tumors in Appalachian children - Huang, Bin (J Neurooncol, 2017)
OBJECTIVE: Determine whether the risk of astrocytomas in Appalachian children is higher than the national average. METHODS: We compared the incidence of pediatric brain tumors in Appalachia versus non-Appalachia regions, covering years 2000–2011. The North American Association of Central Cancer Registries (NAACCR) collects population-based data from 55 cancer registries throughout United States and Canada. All invasive primary (i.e. non-metastatic tumors), with age at diagnosis 0–19 years old, were included. Nearly 27,000 and 2,200 central nervous system (CNS) tumors from non-Appalachia and Appalachia, respectively comprise the cohorts. Age-adjusted incidence rates of each main brain tumor subtype were compared. RESULTS: The incidence rate of pediatric CNS tumors was 8% higher in Appalachia, 3.31 [95% CI, 3.17–3.45] versus non–Appalachia, 3.06, [95% CI, 3.02–3.09] for the years 2001–2011, all rates are per 100,000 population. Astrocytomas accounted for the majority of this difference, with the rate being 16% higher in Appalachian children, 1.77, [95% CI, 1.67–1.87] versus non-Appalachian children, 1.52, [95% CI, 1.50–1.55]. Among astrocytomas, World Health Organization (WHO) grade I astrocytomas were 41% higher in Appalachia, 0.63 [95% CI, 0.56–0.70] versus non-Appalachia 0.44 [95% CI, 0.43–0.46] for the years 2004–2011. CONCLUSIONS AND RELEVANCE: This is the first study to demonstrate that Appalachian children are at greater risk of CNS neoplasms, and that much of this difference is in WHO grade I astrocytomas, 41% more common. The cause of this increased incidence is unknown and we discuss the importance of this in relation to genetic and environmental findings in Appalachia.